Xanthelasma of the stomach - A case report - Dash, Monalisa; Padhee, Ambarish (Indian Journal of Case Reports, 2018)
Gastric xanthelasmas are very uncommon lesions with incidence varying from 0.2% to 0.8%. The lesions are often located in the stomach and less common sites are the esophagus, duodenum, and the colon. Here, we report the case of a 64-year-old female patient, who was admitted to our hospital with symptoms of dysphagia and upper gastrointestinal tract burning sensation. The upper gastrointestinal tract endoscopy revealed fundal erosion. Histopathological examination of the erosive area excluded gastric cancer and revealed numerous large polygonal cells with abundant foamy cytoplasm, and we came to a diagnosis of gastric xanthelasma. Although the clinical significance of gastric xanthelasma is indistinct, similarities with malignancies and association with premalignant lesions exist, we need to forfeit consideration to a diagnosis of xanthelasmas. A biopsy is mandatory and it is advisable to use histochemical and immunohistochemical methods to confirm the diagnosis of xanthelasmas and eliminate the possibility of gastric malignancy.